2013
DOI: 10.1051/0004-6361/201321182
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theory of extremely intermittent pulsars

Abstract: Aims. We investigate whether one or many companions are orbiting the extremely intermittent pulsar PSR B1931+24. Methods. We constrained our analysis on previous observations of eight fundamental properties of PSR B1931+24. The most puzzling properties are the intermittent nature of the pulsar's activity, with active and quiet phases that alternate quasi-periodically; the variation of the slowing-down rate of its period between active and quiet phases; and because there are no timing residuals, it is highly un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…PSR B1931+24 was the first intermittent pulsar discovered; it is known to show normal pulsar behaviour for 5 − 10 days, and then undergo extreme nulling events for 25 − 35 days, making it undetectable (Kramer et al 2006). The possibility that this observed QP behaviour is due to a binary companion of B1931+24 has been studied by Rea et al (2008) and Mottez et al (2013); both concluded that the influence of a companion would not be enough to account for all the properties of the intermittent signal.…”
Section: B1931+24mentioning
confidence: 99%
“…PSR B1931+24 was the first intermittent pulsar discovered; it is known to show normal pulsar behaviour for 5 − 10 days, and then undergo extreme nulling events for 25 − 35 days, making it undetectable (Kramer et al 2006). The possibility that this observed QP behaviour is due to a binary companion of B1931+24 has been studied by Rea et al (2008) and Mottez et al (2013); both concluded that the influence of a companion would not be enough to account for all the properties of the intermittent signal.…”
Section: B1931+24mentioning
confidence: 99%
“…The first discovery of earth-mass exoplanets was indeed around a millisecond pulsar (Wolszczan & Frail 1992). The existence of asteroid belts around millisecond pulsars has been invoked to explain various timing variations and other observational features Shannon et al 2013;Brook 2014;Yu & Huang 2016;Mottez et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…The first discovery of earth-mass exoplanets was indeed around a millisecond pulsar (Wolszczan & Frail 1992a). The existence of asteroid belts around millisecond pulsars has been invoked to explain various timing variations and other observational features (Cordes & Shannon 2008;Shannon et al 2013;Brook et al 2014;Yu & Huang 2016;Mottez et al 2013a).…”
Section: Introductionmentioning
confidence: 99%